2008
DOI: 10.1103/physrevlett.100.048302
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Dissolution of Flow-Induced Precursors

Abstract: We make use of a specially synthesized linear high density polyethylene with a bimodal molecular weight distribution (MWD) to demonstrate that it is possible to produce a suspension of extended-chain (shish) crystals only. Such a suspension can be generated at high temperatures, above but close to the equilibrium melting temperature of the unconstrained extended-chain crystals (T(m)(0)=141.2 degrees C) and requires stretch of the longest chains of the MWD. After the application of a shear flow of 120 s(-1) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
230
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 189 publications
(248 citation statements)
references
References 21 publications
15
230
0
Order By: Relevance
“…The application of flow (shear or elongation) can change drastically the crystallization kinetics and the morphology of semicrystalline polymers (Kumaraswamy et al, 2004;Somani et al, 2005;Kimata et al, 2007;Balzano et al, 2008). Fibrillar precursors, composed of bundles of stretched molecules, are formed when some critical flow conditions are exceeded.…”
Section: Shear-induced Crystallization Using a Slit Rheometermentioning
confidence: 99%
“…The application of flow (shear or elongation) can change drastically the crystallization kinetics and the morphology of semicrystalline polymers (Kumaraswamy et al, 2004;Somani et al, 2005;Kimata et al, 2007;Balzano et al, 2008). Fibrillar precursors, composed of bundles of stretched molecules, are formed when some critical flow conditions are exceeded.…”
Section: Shear-induced Crystallization Using a Slit Rheometermentioning
confidence: 99%
“…35 The formation of a metastable suspension of shishes by imposing the shear close to the thermodynamic melting temperature was also reported by Balzano et al for a bimodal HDPE. 36 The presence of threadlike precursors was proved with rheo-optical techniques by Kornfield et al 17,37 in i-PP melt submitted to duct flow. They observed a peculiar upturn in the birefringence during flow up to a temperature of 215°C; nevertheless, for temperatures higher than 205°C, the flow induced structures relax so fast that no oriented structures were found in the recovered samples.…”
Section: Introductionmentioning
confidence: 99%
“…This notwithstanding, several direct evidences of the existence of long-living metastable structures in sheared polymer melts have been reported. [30][31][32][33][34][35][36][37][38] On segmental scale, rheo-Raman spectra of sheared polyethylene melts indicate the presence of chain sequences in trans conformation, featuring the ordered crystalline state, which persist for several hours after cessation of the shear. 30 Recently, shear-induced conformational ordering in the molten state was also observed in samples of isotactic polypropylene by Li et al [31][32][33] In this case, flow enhances the concentration of long sequences of repeating units in the 3/1 helical conformation required to form the monoclinic crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we studied FIPs in a bimodal polyethylene (PE) melt with this protocol. 35 It was found that FIPs are bundles of stretched chains that, although not crystalline, have a density higher than the melt. In agreement with the classical view on crystallization, 47 after cessation of flow, a selection takes place among FIPs: those exceeding some critical dimensions transform into crystals, whereas the remainders dissolve into the melt.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that stretch of the longest (highest molecular weight) molecules in a undercooled melt promotes shish-kebab formation, but the events in the early stages of the process are not yet fully clarified and certainly not quantified, an important issue for modeling. Several authors invoked the formation of precursors of crystallization, 31,[35][36][37][38][39][40] i.e., an intermediate phase directing the subsequent developments of the crystallization process. For instance, flow-induced precursors (FIPs) were observed by Lee and Schultz 41 studying fiber spinning of poly(ethylene terephthalate) (PET).…”
Section: Introductionmentioning
confidence: 99%